Alterations in the Gut Microbiota of Tibetan Patients With Echinococcosis - Cao, Deping; Pang, Mingquan; Wu, Defang; Chen, Gen; Peng, Xiaohong; Xu, Kai; Fan, Haining (Frontiers in Microbiology, 2022)
There are two main types of echinococcosis, namely alveolar echinococcosis (AE) and cystic echinococcosis (CE). They are zoonotic parasitic diseases caused by the metacestodes of Echinococcus multilocularis and Echinococcus granulosus. In order to explore the gut microbiome composition of patients with echinococcosis, we analyzed fecal samples of seven patients with AE, six patients with CE, and 13 healthy individuals from the Qinghai-Tibetan Plateau, China. Using metagenomic next-generation sequencing, we identified fecal bacteria in the patients with AE and CE. The gut microbiota was analyzed by next-generation metagenomic sequencing (mNGS) to compare patients with either AE or CE against healthy individuals. We found there were some differences between them in abundant bacteria. Our results led to five findings: (1) Between patients with echinococcosis and healthy individuals, the differential bacteria were from four phyla: Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria. (2) Rothia mucilaginosa, Veillonella dispar, Veillonella atypica, Streptococcus parasanguinis, Streptococcus salivarius, and Alistipes finegoldii were abundant in the feces of patients with AE. (3) Bacteroides dorei, Parabacteroides distasonis, Escherichia sp_E4742, and Methanobrevibacter smithii were abundant in the feces of the patients with CE. (4) At the phylum and class level, compared to the AE group, the healthy group was characterized by higher numbers of Actinobacteria. (5) At the family level, Lachnospiraceae and Eubacteriaceae were more abundant in the feces of healthy individuals than in AE patients. The genera Coprococcus, Eubacterium, and Bilophia were more abundant in the healthy group, while the genus Rothia was more abundant in the AE group. The results of this study enrich our understanding of the gut microbiome composition of patients with AE and CE in the Qinghai-Tibetan Plateau.